PENGARUH MOTIVASI, KEMAMPUAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA APARATUR SIPIL NEGARA DINAS KOPERASI, PERINDUSTRIAN DAN PERDAGANGAN KABUPATEN YAHUKIMO - Melpawan Siringoringo; Januarius Resubun (Sekolah Tinggi Ilmu Ekonomi Port Numbay Jayapura, 2016)
Human resources are the most important resources in an institution or organization as the main driver in carrying out organizational functions in order to realize the goals to be achieved. Therefore, all organizations need quality human resources who are able to carry out their duties and responsibilities effectively and efficiently in accordance with their job descriptions. To complete a task or job, a person should have a certain degree of willingness and level of ability. A person's willingness and skills are not effective enough to do something without a clear understanding of what to do and how to do it. Abilities can be innate abilities from birth, or are the result of practice or practice. Human abilities can also be improved by providing the right motivation. Work motivation is needed as one of the performance indicators of the State Civil Apparatus. State Civil Apparatus with high work motivation can be expected to produce maximum performance. To maintain the continuity of the organization's operations, a leader must pay attention and try to influence and encourage the State Civil Apparatus. Giving motivation properly will be able to encourage subordinates to be enthusiastic in carrying out their work, so as to produce something better. Research results Taken together, the variables of motivation, work ability and work discipline can have a positive influence on improving the performance of the State Civil Apparatus at the Department of Cooperatives, Industry and Trade, Yahukimo Regency. This means that if the three variables can be implemented and run well, it will be able to provide morale for the State Civil Apparatus so that it can improve the performance of the State Civil Apparatus for the better in the future. Partially, the variables of motivation, work ability, and work discipline show a significant influence on the performance of the State Civil Apparatus at the Cooperative, Industry and Trade Office of Yahukimo Regency. This indicates that high motivation, good work skills and high work discipline will be able to provide an impetus for the State Civil Apparatus to carry out their duties and responsibilities well so as to produce good performance as well.